Pottery production of the settlement complex of Brigetio - Delbó, Gabriella G. (Dissertationes Archaeologicae, 2021)
Abstract of PhD thesis submitted in 2020 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of László Borhy.